Safety of Systemic Medications Among Older Adults With Psoriasis and Atopic Dermatitis: A Systematic Review of Observational Studies. Issue 4 (July 2021) - Tang, Evan; Maqbool, Talha; Lam, Megan; Adam, Gaelen P.; Tadrous, Mina; Rochon, Paula A.; Drucker, Aaron M.
Background: Psoriasis and atopic dermatitis are common among older adults (≥65 years old), but clinical trials often exclude that population. Objective: To synthesize evidence from observational studies on the safety of systemic therapies (conventional or biologic) for psoriasis and atopic dermatitis among older adults in a systematic review. Methods: We searched MEDLINE and EMBASE (inception to October 31, 2019) and included observational studies reporting adverse events among older people treated with systemic therapy for psoriasis or atopic dermatitis. Outcomes were death, hospitalization, emergency department visits, infections, major cardiovascular events, renal toxicity, hepatotoxicity, and cytopenias. We assessed study quality using the Newcastle-Ottawa Scale. Results: We included 22 studies on treatment for psoriasis and 2 for atopic dermatitis. Most studies were small and non-comparative and 20 of 24 were low quality. Studies comparing safety between medications or medication classes or between older and younger adults did not show apparent differences but had wide confidence intervals around relative effect estimates. Heterogeneity of study design and reporting precluded quantitative synthesis. Conclusions: There is scant evidence on the safety of conventional systemic and biologic medications for older adults with psoriasis or atopic dermatitis; older adults and their clinicians should be aware of this evidence gap.